Komunikasi Corporate Internal Relations PT. AMS Maritime LLC Dalam Menciptakan Work-Life Balance - Yara Mustafa Rahal; Rosanah, Rosanah (Bulletin of Community Engagement, 2024)
This research aims to understand the contribution of Corporate Internal Relations Communication practices at PT. AMS MARITIME LLC in creating work-life balance and its impact on overall employee well-being. Two key components in creating work-life balance in the work environment, namely balancing of time & involvement balancing, and satisfaction balancing, have a significant impact on employee welfare. The research method used is a qualitative approach with data collection through participant observation and light interviews. The research results show that effective internal communication practices are very important in creating conditions that support employee well-being and harmony between work and personal life or work life balance. Keywords: Work Life Balance, Internal Corporate, Corporate Communications